RELATIONSHIP BETWEEN FINANCIAL LITERACY, MATERIALISM, AND IMPULSIVE BUYING ON FINANCIAL BEHAVIOR AND HOW IT INFLUENCES THE FINANCIAL DECISION ON UNDERGRADUATE STUDENTS OF BANDUNG INSTITUTE OF TECHNOLOGY - Naufal Ihsan, Muhammad
Individual requirements and the increasing sophistication of financial products necessitate that everyone be capable of managing their finances effectively. Each individual requires financial literacy, financial behavior, and an excellent financial attitude in order to effectively and efficiently manage and determine attitudes toward limited resources for his or her own well-being. As a result, financial decision-making requires adequate financial literacy and behavior. Additionally, a materialistic attitude contributes to an individual's proclivity for impulsive purchases, which has a detrimental effect on an individual's financial behavior. Youth, such as undergraduate students, are currently undergoing a critical stage in their lives as they strive to achieve financial independence. Undergraduate students must possess a high level of financial literacy and financial behavior in order to make good financial decisions. The purpose of this research is to identify the relationship between financial literacy, materialism, and impulsive buying on financial behavior and how these factors affect the financial decisions of undergraduate students at Bandung Institute of Technology. The sample size for this study is determined using a quantitative methodology and purposive sampling technique. The researcher distributes the questionnaire to 391 Bandung Institute of Technology undergraduate students. The researcher is analyzing the relationship between each variable using descriptive analysis and PLS-SEM analysis. According to this study, 36.83% have a high level of financial literacy, 39.39% have a moderate level of financial literacy, and 23.79% have a low level of financial literacy. There are also differences in financial literacy by gender, with male respondents having a higher level of financial literacy than female respondents, and respondents who major in management having a higher level of financial literacy than respondents who do not major in management. According to the PLS-SEM analysis, undergraduate students' financial literacy has a positive and significant effect on their financial behavior, and the same holds true for the relationship between financial behavior and financial decision-making. Undergraduate financial literacy also has a small but positive effect on financial decision-making. Additionally, the research discovered that materialism and impulsive buying have a negative effect on undergraduate financial behavior, particularly on impulsive buying. Additionally, impulsive purchasing acts as a moderating factor in the relationship between materialism and financial behavior. Because ITB undergraduate students already possess a high level of financial literacy, financial behavior, and financial decision-making, the university is able to maintain this level through the provision of quality financial education programs.